2020
DOI: 10.12659/msm.922137
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Synuclein Levels Are Elevated in Peritoneal Fluid of Patients with Endometriosis

Abstract: Departmental sources Background:The role of gamma-synuclein (SNCG) has been widely examined in malignant conditions due to its possible role in disease progression, but very little information is available on its theoretical function on endometriosis formation. Material/Methods:Between January 2016 and December 2016, we collected peritoneal fluid and plasma samples from 45 consecutive female patients, of which 15 were without endometriosis, 15 had minimal to mild endometriosis, and 15 had moderate to severe en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…In addition to attraction of immune cells, our data suggests these CCL19 + perivascular cells likely promote angiogenesis through angiopoietin expression, presumably targeting endothelial tip cells in the peritoneal microenvironment that express the corresponding receptors. In further support of these cells playing an active role in lesion vascularization and growth, it has been shown that inhibition of SNCG reduces these features in endometriosis 62 , and our data indicate SNCG is uniquely expressed by this CCL19 + perivascular population. The regulation of angiogenesis through secretion of pericyte-derived pro-angiogenic factors was previously demonstrated in in vitro proinflammatory microenvironments 63 and here we illustrate in vivo angiogenesis modulation by perivascular cells in peritoneal endometriosis.…”
Section: Discussionsupporting
confidence: 75%
“…In addition to attraction of immune cells, our data suggests these CCL19 + perivascular cells likely promote angiogenesis through angiopoietin expression, presumably targeting endothelial tip cells in the peritoneal microenvironment that express the corresponding receptors. In further support of these cells playing an active role in lesion vascularization and growth, it has been shown that inhibition of SNCG reduces these features in endometriosis 62 , and our data indicate SNCG is uniquely expressed by this CCL19 + perivascular population. The regulation of angiogenesis through secretion of pericyte-derived pro-angiogenic factors was previously demonstrated in in vitro proinflammatory microenvironments 63 and here we illustrate in vivo angiogenesis modulation by perivascular cells in peritoneal endometriosis.…”
Section: Discussionsupporting
confidence: 75%
“…In addition to attraction of immune cells, our data suggests these CCL19 + perivascular cells likely promote angiogenesis through angiopoietin expression, presumably targeting endothelial tip cells in the peritoneal microenvironment that express the corresponding receptors. In further support of these cells playing an active role in lesion vascularization and growth, it has been shown that inhibition of SNCG reduces these features in endometriosis 62 , and our data indicate SNCG is uniquely expressed by this CCL19 + perivascular population.…”
Section: Discussionsupporting
confidence: 75%
“…In contrast with SNCA and SNCB, SNCG is not only connected to neurodegenerative disorders, like Alzheimer's disease and Parkinson's disease [16], but also primarily relates to various human tumors and participates in cancer occurrence and progression [17]. For example, studies have proved that SNCG is significantly higher expressed in advanced breast cancer samples and peritoneal fluid of endometriosis patients [18], meanwhile, it can facilitate the metastasis of breast cancer [19,20]. The expression of SNCG is also elevated in high-grade serous patients.…”
Section: Discussionmentioning
confidence: 99%